Orientation of Islamic Education Curriculum and Its Relevance with the Qur'an - Mardiah, Mardiah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
The curriculum is one of the important components of an education system. The curriculum must be planned and designed as well as possible in order to be able to direct students to achieve the learning and educational goals that have been set. Students must be directed to become perfect people and comprehensive people. This research aims to find the differences between the general curriculum and the Islamic education curriculum and which curriculum is most suitable for Islamic education. The method used in this research is a qualitative method by reviewing various references about the curriculum. The results showed that, in the Islamic education curriculum, the basis for preparing the curriculum must meet the religious and organizational basis in addition to the philosophical, psychological, and sociological basis. The curriculum model in accordance with Islamic education is an integrated curriculum (integrated) that integrates all subjects to find solutions to human problems.